Post-Soviet trends in the development of nonformal education of children and youth: Belarusian case - Yakovlevа, Irina A. (Journal of the Belarusian State University. Sociology, 2021)
In this article the author analyses the processes of sociogenesis and transformation of the system of additional education for children and youth in the social-temporal continuum which is set by the challenges of the post-Soviet period of the formation of the Republic of Belarus as a sovereign state. The main socio-cultural formats and trends of innovative development of additional education that presented as a social system and socio-educational practice were studied. The author explores methodological approaches to the analysis of additional education as a variable polydisciplinary type of education which is not regulated by state educational standards. Today additional education is considered as a social technology of formal education, non-formal education and development. The article provides up-to-date statistical information about social actors who implement additional education for children and youth in the Republic of Belarus. This approach allows us to consider additional education as a sociosphere of resource opportunities that increase the efficiency of socialisation process of students.
Keywords: non-formal education of children and youth; social time; innovative trends of social development; availability and quality of non-formal education of children and youth; social technology; sociosphere of personality development